Investigation of the Mechanism of Action of AMPs from Amphibians to Identify Bacterial Protein Targets for Therapeutic Applications - Carolina Canè; Lidia Tammaro; Angela Duilio; Angela Di Somma (MDPI AG, 2024)
Antimicrobial peptides (AMPs) from amphibians represent a promising source of novel antibacterial agents due to their potent and broad-spectrum antimicrobial activity, which positions them as valid alternatives to conventional antibiotics. This review provides a comprehensive analysis of the mechanisms through which amphibian-derived AMPs exert their effects against bacterial pathogens. We focus on the identification of bacterial protein targets implicated in the action of these peptides and on biological processes altered by the effect of AMPs. By examining recent advances in countering multidrug-resistant bacteria through multi-omics approaches, we elucidate how AMPs interact with bacterial membranes, enter bacterial cells, and target a specific protein. We discuss the implications of these interactions in developing targeted therapies and overcoming antibiotic resistance (ABR). This review aims to integrate the current knowledge on AMPs' mechanisms, identify gaps in our understanding, and propose future directions for research to harness amphibian AMPs in clinical applications.